Dialectics of nature: The emergence of policy on the management of commercial fisheries in english European Marine Sites. (April 2017) - Clark, Robert; Humphreys, John; Solandt, Jean-Luc; Weller, Catherine
Abstract: European Marine Sites (EMS), designated under either the Habitats or Birds Directives, protect the biodiversity of the European Union (EU) and contribute to the implementation of the 1992 UN Convention on Biological Diversity[1] . The introduction of this form of marine protected area (MPA), as a consequence of EU conservation directives, introduced new legal obligations in waters long exploited by inshore fishing communities. Although the Habitats and Birds Directive have been in place since 1992 and 1979 respectively (the 1979 Directive updated in 2009), it has not been until more recently (2014) that ongoing inshore fisheries activities in England, which predate designation of sites, have been systematically assessed and managed, for their impact in protected sites. In practice it was assumed by many MPA practitioners that at the time of designation of EMS, ongoing activities would be compatible with the conservation objectives of these sites. This paper illustrates the introduction of a general and systematic "revised approach" to managing fisheries in all English EMSs, and how this represented a change in government policy which can be traced directly to a legal campaign between 2008 and 2012 by two UK environmental Non-Governmental Organisations (eNGOs). The paper elucidates this iterative marine policy process analysing the dialogue between government bodies and eNGOs and show how the resulting interpretation of conservation law, has sought to resolve the tensions between the precautionary approach as emphasised by the eNGOs and the Government's desire for proportionality of response.